2013
DOI: 10.1111/1471-0528.12189
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and the risk for recurrent pre‐eclampsia: a retrospective cohort study

Abstract: Interpregnancy metabolic syndrome predisposes to recurrent pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…8 On the other hand, a predisposition to the metabolic syndrome may induce women to develop preeclampsia during pregnancy. [9][10][11] Several studies have shown an association between maternal preeclampsia and elevated blood pressure (BP) in the offspring during childhood and adolescence. [12][13][14][15][16][17][18][19] Other studies have reported on glucose metabolism in the offspring of mothers with preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…8 On the other hand, a predisposition to the metabolic syndrome may induce women to develop preeclampsia during pregnancy. [9][10][11] Several studies have shown an association between maternal preeclampsia and elevated blood pressure (BP) in the offspring during childhood and adolescence. [12][13][14][15][16][17][18][19] Other studies have reported on glucose metabolism in the offspring of mothers with preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…For example, increased oxidative stress is seen in diabetes mellitus, hypertension and coronary heart disease insulin resistance (75,76), hypertension, elevated levels of pro-inflammatory cytokines (79,80) and incidence of type 2 diabetes mellitus is high in them (81,82). This indicates that preeclampsia is a disease in which factors that are involved in the pathogenesis of insulin resistance, hypertension, type 2 diabetes mellitus and low-grade systemic inflammation play a significant role.…”
Section: Angiotensin-1 Receptor In Pre-eclampsiamentioning
confidence: 99%
“…11 Recently there has been a study which demonstrates that inter-pregnancy metabolic syndrome predisposes to preeclampsia which further substantiates the fact that these two disorders share a common pathophysiology. 12 By elucidating the association of metabolic syndrome with severity of preeclampsia it may be possible to understand the pathophysiology and potentially predict the development of severe pre-eclampsia.…”
Section: Introductionmentioning
confidence: 84%